Body mass index, playing position, race, and the cardiovascular mortality of retired professional football players - Baron, S. L.; Hein, M. J.; Lehman, E.; Gersic, C. M. (The American Journal of Cardiology, 2012)
Concern exists about cardiovascular disease (CVD) in professional football players. We examined whether playing position and size influence CVD mortality in 3,439 National Football League players with =5 pension-credited playing seasons from 1959 to 1988. Standardized mortality ratios (SMRs) compared player mortality through 2007 to the United States population of men stratified by age, race, and calendar year. Cox proportional hazards models evaluated associations of playing-time body mass index (BMI), race, and position with CVD mortality. Overall player mortality was significantly decreased (SMR 0.53, 95% confidence interval [CI] 0.48 to 0.59) as was mortality from cancer (SMR 0.58, 95% CI 0.46 to 0.72), and CVD (SMR 0.68, 95% CI 0.56 to 0.81). CVD mortality was increased for defensive linemen (SMR 1.42, 95% CI 1.02 to 1.92) but not for offensive linemen (SMR 0.70, 95% CI 0.45 to 1.05). Defensive linemen's cardiomyopathy mortality was also increased (SMR 5.34, 95% CI 2.30 to 10.5). Internal analyses found that CVD mortality was increased for players of nonwhite race (hazard ratio 1.69, 95% CI 1.13 to 2.51). After adjusting for age, race, and calendar year, CVD mortality was increased for those with a playing-time BMI =30 kg/m2 (hazard ratio 2.02, 95% CI 1.06 to 3.85) and for defensive linemen compared to offensive linemen (hazard ratio 2.07, 95% CI 1.24 to 3.46). In conclusion, National Football League players from the 1959 through 1988 seasons had decreased overall mortality but those with a playing-time BMI =30 kg/m2 had 2 times the risk of CVD mortality compared to other players and African-American players and defensive linemen had higher CVD mortality compared to other players even after adjusting for playing-time BMI.